Effects of using rigid tape with bandaging techniques on wrist joint motion during boxing shots in elite male athletes - Gatt, I. T.; Allen, T.; Wheat, J. (Physical Therapy in Sport, 2023)
Highlights • This is the first study confirming bandaging effects on wrist kinematics in boxing.